Fibrin Polymerization Defect in HIV-infected Patients-Evidence for a Critical Role of Albumin in the Prolongation of Thrombin and Reptilase Clotting Times - Toulon, Pierre; Frere, Elyane; Bachmeyer, Claude; Candia, Nathalie; Blanche, Philippe; Sereni, Daniel; Sicard, Didier (Thrombosis and Haemostasis, 1995)
Thrombin clotting time (TCT) and reptilase clotting time (RCT) were found significantly prolonged in a series of 72 HIV-infected patients drawn for routine coagulation testing. Both TCT and RCT were highly significantly correlated with albumin (r = -0.64, and r = -0.73 respectively, p<0.0001). TCT and RCT were significantly higher (p<0.0001) in a series of 30 other HIV-infected patients selected on their albumin level below 30.0 g/l (group l) than in 30 HIV-infected patients with albumin level above 40.0 g/l or in 30 HIV-negative controls; the two latter groups were not different. In vitro supplementation of plasma from group 1 patients with purified human albumin up to 45.0 g/l (final concentration) lead to a dramatic shortening effect on both TCT and RCT, which reached normal values. The TCT and RCT of the purified fibrinogen solutions (2.0 g/l final concentration) were not different in the three groups, and normal polymerization curves were obtained in all cases. This further ruled out the presence of any dysfibrinogenemia in the plasma from group 1 patients. Using purified proteins, highly significant correlations were demonstrated between the albumin concentration and the prolongations of both TCT and RCT, which were of the same magnitude order than those found in the patients plasma. These results suggest that hypo-albuminemia is responsible for the acquired fibrin polymerization defect reported in HIV-infected patients. The pathophysiological implication of the low albumin levels was suggested by the finding of decreased albumin levels (associated with prolonged TCT and RCT) in a small series of the eight HIV-infected patients who developed thrombotic complications.